Advancing towards ready-to-use solid oxide fuel cells: 5 minute cold start-up with high-power performance. Issue 14 (27th March 2023) - Jeong, Hyeseong; Lee, Channyung; Son, Ji-Won; Lee, Seung Yong; Yoon, Kyung Joong; Shin, Dongwook; Choi, Mansoo; Shin, Sung Soo; Kim, Hyoungchul
Abstract : This study reports a high-performance solid oxide fuel cell system with rapid thermal cycling and cold start-up ( i.e., ready-to-use) for mobile applications. This system reached 600 °C within 5 min of start-up and exhibited maximum power of 1.123 W. Abstract : The development of low-temperature solid oxide fuel cells (LT-SOFCs) as a mobile power source is attracting attention; however, limited understanding of rapid LT-SOFC operation constrains their use. Here, we present a high-performance LT-SOFC system capable of rapid thermal cycling and cold start-up, akin to ready-to-use. To achieve a ready-to-use LT-SOFC system, we modified a compact compressive sealing architecture implemented with a stacked disc spring, and a rapid thermal cycling with cold start-up was realized using a lamp heater. This LT-SOFC system reached target temperatures within 5 min of start-up and immediately exhibited an open-circuit potential of 1.124 V and a maximum power density of 1.123 W cm −2 at 600 °C. We evaluated this system with harsh thermal cycling (25–500 or 600 °C) for 3000 min and confirmed its degradation behavior in perovskite phase separation and interfacial delamination. Our results provide another breakthrough in LT-SOFC development for mobile applications.